If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -13 = 38 Reorder the terms: -13 + y = 38 Solving -13 + y = 38 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + y = 38 + 13 Combine like terms: -13 + 13 = 0 0 + y = 38 + 13 y = 38 + 13 Combine like terms: 38 + 13 = 51 y = 51 Simplifying y = 51
| 2y(2y-9)+(2y-9)= | | 2x/5-5=4 | | 3b^2+6b+3= | | f+43=120 | | 6n+21=4n+1 | | e-35=27 | | 0.000054s= | | d+19=83 | | k^2-36= | | f+27=49 | | 26/100= | | 0.10(y-8)+0.18y=0.12y-0.03(40) | | 3x^2+5x+k= | | 5+d=71 | | I=(1535)(.045)(3) | | 0.50x+0.80(60)=0.25(116) | | -20-40=-21/4 | | -40x+5y=30 | | -40=-21/4(x-20) | | (x-3/2)^2 | | -40=-21/4(x-20 | | x/3+2x/9+4x/27+8x/81+1=x | | 5p+(-6)= | | -sin(6x)=0 | | 3n^3/n^3 | | (-2r)(8)+(25)= | | 4/2-4/5= | | 9=8m+9 | | -3(-4-6y)+7(-4+5)=-8 | | 4/21*(145-y) | | X+(-4)+6x=3x+(-1)+5 | | 5-(x+7)=5x-8 |